2020
DOI: 10.1016/j.ecoleng.2020.105741
|View full text |Cite
|
Sign up to set email alerts
|

When “safe” dams kill: Analyzing combination of impacts of overflow dams on the migration of silver eels

Abstract: 1. The drastic decline in European eel Anguilla anguilla stock is now widely recognized. However, while various causes for this decline have been identified, the relative importance of each cause remains unclear. 2. During the catadromous migration of silver eels, the negative impact of dams is frequently highlighted, but mainly for powered dams (with turbines) or where connectivity is completely ruptured. Mechanical impact due to turbine blades is often considered the most important cause of mortality of silv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…A gap between predicted and actual migration can also occur when migration delays are induced by obstacles and management actions (e.g. sluice gate operations, dams, and water reservoirs; Trancart et al, 2020), e.g. in the Vilaine River (dam generating an abrupt discontinuity in the estuarine-fluvial gradient) or in the Somme River (recurrent artificial discharge peaks).…”
Section: Management Implication and Transferabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…A gap between predicted and actual migration can also occur when migration delays are induced by obstacles and management actions (e.g. sluice gate operations, dams, and water reservoirs; Trancart et al, 2020), e.g. in the Vilaine River (dam generating an abrupt discontinuity in the estuarine-fluvial gradient) or in the Somme River (recurrent artificial discharge peaks).…”
Section: Management Implication and Transferabilitymentioning
confidence: 99%
“…While river obstruction affects accessibility of catchments during upstream migration, dams and hydropower turbines are also sources of mortality during downstream movement (Eyler et al, 2016;Feunteun et al, 2000;Song et al, 2019). Even without power plants, reservoir dams can temporarily or permanently stop fish migration (Acou et al, 2008;Besson et al, 2016;Trancart et al, 2020). By accounting for the influence of environmental cues or behavioural settings, several predictive models have been developed to predict migration events for several diadromous species, including white sturgeon (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species is considered critically endangered [7]. Their decline is associated with the drastic negative effect of habitat loss, hydropower, overfishing, climate change, pollution, parasites and diseases on spawning stock size [7,8]. Eel spawning stock is determined by the number of migrating silver eels (escapement) from the waters of North Africa to the northern tip of Scandinavia [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…are favourable and the predation risk is minimal [4]. Failures in migration timing, including delays caused by man-made obstacles, can be costly [8]. It has been shown that the timing of migration is adjusted according to the conditions in freshwaters, estuaries and marine waters [1216].…”
Section: Introductionmentioning
confidence: 99%